CRISPR/Cas9-Mediated Chicken TBK1 Gene Knockout and Its Essential Role in STING-Mediated IFN-β Induction in Chicken Cells - Cheng, Yuqiang; Lun, Minxiang; Liu, Yunxia; Wang, Hengan; Yan, Yaxian; Sun, Jianhe (Frontiers in Immunology, 2019)
TANK‐binding kinase 1 (TBK1) is involved in innate immunity, prompting transcriptional induction of type I interferons in response to pathogenic infection. Many studies have focused on mammals but the function of TBK1 in chickens remains poorly defined. CRISPR/Cas9 system has made gene-knockout easy to accomplish. Although CRISPR/Cas9 has been used in chicken cells, low mutation efficiency limits its wide application in chickens. In this study, an effective gene-knockout system was developed based on the CRISPR/Cas9 system in chicken embryonic fibroblast DF-1. Two CRISPR/Cas9 plasmids were constructed, TBK1-g1 and TBK1-g2, which express gRNAs targeting different sequences of the chicken TBK1 gene. After transfection and enrichment with puromycin screening, the mutation rates as assessed via T7E1 assay were 88.05% and 89.55%, respectively, and subsequent sequence analysis showed mutation efficiencies of 86.67% and 93.33%. With the limiting-dilution method, a chTBK1 gene-deficiency monoclonal cell line was obtained and was named DF-1-TBK1-C3. The DF-1-TBK1-C3 cells exhibited normal morphology and maintained stable proliferation ability compared to wild-type cells. The gene-overexpression system and luciferase reporter assay showed that IFN-β induction induced by chSTING was almost completely blocked in DF-1-TBK1-C3 cells. With quantitative real-time PCR, we further confirmed the essential role of chTBK1 in the chSTING-mediated IFN-β induction. At last, the study demonstrated that the chTBK1 knockout system is also applicable in primary chick embryo fibroblasts (CEFs). In this study, an effective gene-knockout system was applied in chickens, a TBK1 gene-deleted DF-1 cell line was successfully created using this system, and with the chTBK1 knockout cells, chTBK1 was revealed to be indispensable in STING-mediated IFN-β activation in chicken cells.